Origin of seafloor pockmarks overlying submarine landslides: Insights from semi-automated mapping of 3D seismic horizons (North West Shelf, Australia). (February 2022) - Riera, Rosine; Paumard, Victorien; de Gail, Myriam; Saqab, Muhammad Mudasar; Lebrec, Ulysse; Lang, Simon C.; Lane, Andy
Abstract: Pockmarks are geohazards that can impact offshore developments, and an understanding of their formation assists in determination of their physical characteristics and in the prediction of their future behaviour. This study documents how the presence of submarine landslides - either on the seafloor or buried - can favour pockmark formation through the characterisation of two pockmark fields from the Australian North West Shelf. Analysis was carried out through an innovative workflow combining full-volume interpretation of exploration 3D seismic data and semi-automated mapping of seismic horizons. The Gorgon Pockmark Field (GPF) extends over ∼125 km 2 in water depths ranging from 210 to 480 m. It contains ∼500 pockmarks with diameters of ∼150–200 m. The pockmark field overlies a submarine landslide and was likely created by the expulsion of fluids and/or liquefied sediment during or after the formation of the landslide. The Carnarvon Pockmark Field (CPF), located 100 km southwest of the GPF, covers around ∼150 km 2 in water depth ranging from 680 to 930 m. It contains ∼250 pockmarks, each having a diameter of ∼250–300 m. The CPF developed on a buried paleo-landslide. While the seafloor pockmarks and the paleo-landslide are physically disconnected by a sedimentary drape, seafloor pockmarks are abundant above the paleo-landslide and present a characteristic morphology, then suggesting that fluids circulating through the paleo-landslide induced the formation of the seafloor pockmarks. Study of the Gorgon and Carnarvon pockmark fields presents new evidence that submarine landslides - either on the seafloor or buried - can control the development of pockmarks over huge areas of the seafloor. Graphical abstract: Image 1 Highlights: Pockmark fields >100 km 2 developed on submarine landslide and paleo-landslide in Australian NWS. Mapping of 3D seismic horizons indicates pockmark morphology is specific to each landslide. New evidence that formation of a submarine landslide can trigger pockmark development. Buried paleo-submarine landslides can also control the organisation of seafloor pockmarks. Behaviours possibly enabled by the presence of small amount of gas in the sediment.